Effects of rotation and MHD on the Nonlinear Peristaltic Flow of a Jeffery Fluid in an Asymmetric Channel through a Porous Medium - M. Abdulhadi, Ahmad; Al-Hadad, Aya H. (Iraqi Journal of Science, 2023)
In this paper, the effect of both rotation and magnetic field on peristaltic transport of Jeffery fluid through a porous medium in a channel are studied analytically and computed numerically. Mathematical modeling is carried out by utilizing long wavelength and low Reynolds number assumptions. Closed form expressions for the pressure gradient, pressure rise, stream function, velocity and shear stress on the channel walls have been computed numerically. Effects of Hartman number, time mean flow, wave amplitude, porosity and rotation on the pressure gradient, pressure rise, stream function, velocity and shear stress are discussed in detail and shown graphically. The results indicate that the effect of Hartman number, time mean flow, wave amplitude, porosity and rotation are very pronounced in the phenomena, when we change a Jeffery fluid to second order fluid we obtain the results of [1].